Manganese exposure and working memory-related brain activity in smallholder farmworkers in Costa Rica: Results from a pilot study - Palzes, Vanessa A. (Environ Res, 2019)
Main sources of manganese (Mn) in the general population are diet and drinking water. Mn is also found in ethylene bisdithiocarbamate (EBDC) fungicides used in agriculture or emitted into the air by ferromanganese plants and welding fumes, which can be additional environmental and occupational sources of exposure. High occupational Mn exposure has been linked with motor, behavioral, and cognitive impairment, but its effects on neural function remain poorly understood. We conducted a functional neuroimaging study in a sample of 48 farmworkers in Zarcero County, Costa Rica, an agricultural region where EBDC fungicides are sprayed. We measured Mn concentrations in farmworkers’ toenails (n = 40 farmworkers) and hair (n = 33 farmworkers), and recorded brain activity in the dorsolateral prefrontal cortex during a letter-retrieval working memory task using functional near-infrared spectroscopy (fNIRS). We estimated exposure-outcome associations using multivariable linear regression models adjusted for age and education level. Geometric mean (geometric standard deviation) toenail and hair Mn concentrations were 0.40 μg/g (3.52) and 0.24 μg/g (3.54), respectively. We did not find strong evidence that Mn concentrations were associated with working memory-related brain activity in this sample of farmworkers; we also found null associations between working memory task accuracy and brain activity. However, our small sample size may have limited our ability to detect small effect sizes with statistical precision. Our study demonstrates that fNIRS can be a useful and feasible tool in environmental epidemiology for examining the effects of toxicants, like Mn, on neural function. This may prove to be important for elucidating neuropathological pathways that underlie previously reported associations of elevated Mn exposure with neurotoxic effects.